Data Analytics for the Cryptocurrencies Behavior - Sánchez, Eduardo (2019)
The cryptocurrencies are a new paradigm of transferring money be-tween users. Their anonymous and non-centralized is a subject of debate around the globe that paired with the massive spikes and declines in value that are in-herit to an unregistered asset. These facts make difficult for the common daily use of the cryptocurrencies as an exchange currency as instead they are being used as a new way to invest. What we propose in this article is a system for the better understanding of the cryptocurrencies economical behavior against the global market. For that we are using Data Analytics techniques to build a pre-dictor that uses as inputs said external financial variable. These forecasts would help determine if a coin is safe to trade with, if those forecasts can be precise by only using this external data. The results obtained indicates us that there is a certain degree of influence of the global market to the cryptocurrencies, but that is it not enough to correctly predict the fluctuations in price of the coins and that they care more about others factors and that they have their own bubbles, like the crypto collapse in late 2017.